trans-Fluorine Effect in Cyclopropane: Diastereoselective Synthesis of Fluorocyclopropyl Cabozantinib Analogs - Veliks, Janis; Videja, Melita; Kinens, Artis; Bobrovs, Raitis; Priede, Martins; Kuka, Janis (ACS medicinal chemistry letters, 2020)
Investigation of the trans-fluorine effect on the hydrolysis rate of diethyl 2-fluorocyclopropane-1,1-dicarboxylate provides synthetic access to both diastereomers of the fluorocyclopropyl analog of cabozantinib, a c-Met and VEGFR-2 inhibitor used as a first-line treatment for thyroid cancer and as a second-line treatment for renal cell carcinoma. Despite some known potent examples, there are only a few drug molecules that contain fluorocyclopropane moieties. Herein, we present a case study in which the monofluoro analog of a known cyclopropane-containing drug molecule displays an improved in vitro profile compared to the parent nonfluorinated structure. The fluorocyclopropane moiety may offer valuable fine-tuning options for lead optimization in drug discovery.